If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 3(2x + 4) = 47 Reorder the terms: x + 3(4 + 2x) = 47 x + (4 * 3 + 2x * 3) = 47 x + (12 + 6x) = 47 Reorder the terms: 12 + x + 6x = 47 Combine like terms: x + 6x = 7x 12 + 7x = 47 Solving 12 + 7x = 47 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 7x = 47 + -12 Combine like terms: 12 + -12 = 0 0 + 7x = 47 + -12 7x = 47 + -12 Combine like terms: 47 + -12 = 35 7x = 35 Divide each side by '7'. x = 5 Simplifying x = 5
| 3(2m-1)+m=m-3 | | 46+4x=-6x | | 8+3y=-7 | | findvc=kpv | | [5x+8]=x+12 | | 4(3m-5)-m=-m+16 | | (25)+(x+15)=(3x-10) | | Y=-0.414(70)+106.55 | | -1(x+m)=3(x+9)-10 | | 3x+-4=x+2 | | -85=5(1-3x) | | 18-(3-2m)=3(m-5) | | 100[0.03(p+4)]= | | [3x]=-27 | | 6m+2(4-2m)=3(m+4) | | 3/8-5/6= | | 2v^2-11v-40=0 | | -(3w-2)-w=30 | | 3.5+32.1=4.9-10.1x | | 8(2n+5)=6(6n+4)+2 | | Factorx^2+2x+100=0 | | 25x+15=3x-10 | | log(y)=-3log(x) | | 27=-4x+7x-6 | | 15=8+.75x | | 5-3(4-2m)=4(m-3)-3 | | 5m+3(m-2)=6m-12 | | -2-7a=8-5a | | 5(2n+3)=8(6n+1)+4 | | -184=6-8(7-8n) | | -2m-13-8(m-4)=7m-(8m-3)-6m+1 | | 7m-(9-4m)=3(m-11) |